Definitions and Outcome Measures of Clinical Trials Regarding Opioid-induced Constipation. Issue 1 (January 2015) - Gaertner, Jan; Siemens, Waldemar; Camilleri, Michael; Davies, Andrew; Drossman, Douglas A.; Webster, Lynn R.; Becker, Gerhild
<x xml:space="preserve">Abstract</x> Opioid-induced constipation (OIC) is a frequent symptom in patients treated with opioids and impacts the patients' quality of life. However, there is no generally accepted definition for OIC. The aims of this study were to identify definitions for OIC in clinical trials and Cochrane Reviews and to compile assessment tools and outcome measures that were used in clinical trials. In a systematic review, 5 databases (MEDLINE, PubMed, The Cochrane Library, Web of Science, and EMBASE) were searched to identify clinical trials assessing OIC in adult patients or healthy volunteers. Studies published between 1993 and August 2013 were included. A total of 1488 studies were retrieved and 47 publications were included in the analysis. A minority of the publications (n=16, 34%) provided a clear definition for OIC. The definitions were highly variable and the present or recent history of opioid therapy was frequently (n=6, 38%) not included in these definitions. Of 46 clinical trials, 17 (37%) relied exclusively on objective measures such as bowel movement frequency, whereas another 17 studies additionally included patient-reported outcome measures such as, "feeling of incomplete bowel evacuation." Few trials (n=7, 15%) assessed the patient-reported global burden of OIC. Standard definitions and outcome measures are necessary (i) for consistency in OIC diagnosis in clinical practice and clinical trials; and (ii) to assure comparability of trial findings (eg, in meta-analyses). An OIC definition and outcome measures are proposed.